Analysis of the Effectiveness of Agile Supply Chain in Indonesia’s Largest Shipbuilding Industry - Sutjipto; Baroroh, Intan (International Journal of Marine Engineering Innovation and Research, 2025)
The shipbuilding industry is currently facing increasingly complex challenges, particularly related to market demand dynamics, global competition, and production timeliness. The implementation of Agile Supply Chain (ASC) is expected to be a strategic solution to address these challenges because ASC can increase flexibility and response to rapid changes and high demand variability. This study aims to analyze the Supply Chain Management (SCM) process in the largest shipbuilding industry in Indonesia, with a focus on identifying challenges in ASC implementation and examining the role of information technology in supporting this framework. A mixed methods approach is employed to investigate these issues by collecting data through questionnaires, in-depth interviews, direct observation, and analysis of relevant documents. The research findings indicate that ASC implementation, with collaboration and integration technology as the most dominant variables, can significantly improve operational flexibility, accelerate production timelines, reduce reliance on inventory, ensure timely material arrivals, and improve coordination among stakeholders in the supply chain. In addition, the adoption of ASC can result in faster ship construction compared to the initial planning stage. Challenges faced in implementing ASC include the need for investment in technological infrastructure, workforce training, and organizational culture transformation. Training, effective communication, and investment in supply chain digitalization systems are essential to improve the effectiveness of ASC implementation, thereby supporting the competitiveness and efficiency of the Indonesian shipbuilding industry in the future.